Lumbar drain for CSF leakage: A word of caution - Chashamjot Bawa Chasham; Jyoti Raina Jyoti; Amandeep Singh Randhawa Aman; Khushbu Rani Khushbu (Indoscholar, 2021)
Continuous lumbar drain is a frequently practiced procedure to prevent cerebrospinal fluid (CSF) infection in post-operative neurosurgical cases. However, the level of CSF drained must correspond to the intracranial pressures, where any accidental increase in lumboventricular gradient by slipping of the drainage bag below the level of the iliac crest can lead to over drainage and catastrophe. The learning point is to use automated or manual measures to monitor Intra-Cranial Pressure (ICP) and sound alarm in such an event to prevent sagging of the brain.